Ensuring compliance with the Water Framework Directive when regulating pollutant discharges into wastewater - Yurasov, S. M.; Terzeman, V. V. (Man and Environment. Issues of Neoecology, 2025)
Purposes. Development of scientifically based proposals for taking into account the conditions of the Water Framework Directive of the European Union and river basin management plans when calculating maximum permissible discharges of pollutants with wastewater using domestic methods.Methods. Statistical, as well as methods of mathematical modelling and forecasting.Results. According to the provisions of the Water Framework Directive and at the initial stage of river basin management plans, the quality of water in a water body for a certain past period is considered to meet the requirements of EU standards if the probability of exceeding (security) of the standards for each indicator does not exceed the specified limit F. Based on this, it is proposed to carry out standardization, as well as the associated assessment and forecasting of surface water quality using indicators with security F. This approach ensures the coordination of domestic methods of the aforementioned calculations with the requirements of EU legislation. The proposed provisions are tested on the example of the analysis of the temporal variability of water quality indicators of the Danube rivers (according to observations during 2015–2024) and the Dniester (according to retrospective observations of 2001–2017). It is shown that when using average values of indicators, the requirements of the Water Framework Directive and river basin management plans are often not met, since the provision of these values can significantly exceed the established restrictions on the frequency of exceedances of the maximum permissible concentration. To gradually achieve "good status" of surface water bodies when regulating pollutant discharges with wastewater, it is advisable to use the values of indicators with a provision of 10%, 5% and 2.5% as calculated (background). At the same time, in the presence of time trends of indicators, it is necessary to forecast their values to ensure the requirements of the Water Framework Directive, especially with positive trends.Conclusions. According to the requirements of the Water Framework Directive and river basin management plans, in order to gradually achieve good status of surface water bodies at the initial stage, it is advisable to take the value of F equal to 10%, 5% and 2.5%. It is advisable to standardize pollutant discharges taking into account the time trends of indicators, since ignoring a positive trend leads to an overestimation of the calculated values, which is unacceptable, while the presence of a negative trend, on the contrary, leads to their underestimation, which is acceptable from the point of view of environmental protection.